2013
DOI: 10.3758/s13414-013-0507-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fatigue on the attentional blink

Abstract: It has been suggested that attention and emotional states are tightly linked, in that negative moods are associated with narrowed attentional focus, whereas positive moods are associated with broadened focus. However, recent studies on the effect of affective states, using the attentional blink deficit as a reflection of the temporary unavailability of attentional resources, have reported ambiguous results regarding the deployment of attention in the temporal domain. In the present study, we examined whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The three moods selected for the study occupy the broad category of negative affect but exhibit subtle differences on dimensions of valence and arousal, captured in Russell's circumplex model. Numerous studies have classified sadness, fatigue, and anxiety as moods within the valence/arousal model (Vuoskosi & Eerola, 2011;Sandstrom & Russo, 2010;Feldman Barrett & Russell, 1998;Kawahara & Sato, 2013;Russell, 2003;Posner, Russell & Peterson, 2005).…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The three moods selected for the study occupy the broad category of negative affect but exhibit subtle differences on dimensions of valence and arousal, captured in Russell's circumplex model. Numerous studies have classified sadness, fatigue, and anxiety as moods within the valence/arousal model (Vuoskosi & Eerola, 2011;Sandstrom & Russo, 2010;Feldman Barrett & Russell, 1998;Kawahara & Sato, 2013;Russell, 2003;Posner, Russell & Peterson, 2005).…”
Section: Classificationmentioning
confidence: 99%
“…Within the affective space of Russell's circumplex, fatigue is lowest in arousal and has neutral or slightly negative valence (Feldman Barrett & Russell, 1998;Kawahara & Sato, 2013). Fatigue can manifest both physiologically and cognitively (Sharpe & Wilks, 2002;Carney, Moss, Lachowski & Atwood, 2010).…”
Section: Fatiguementioning
confidence: 99%
“…The three moods selected for the study occupy the broad category of negative affect but exhibit subtle differences on dimensions of valence and arousal, captured in Russell's circumplex model. Numerous studies have classified sadness, fatigue, and anxiety as moods within the valence/arousal model (Vuoskosi & Eerola, 2011;Sandstrom & Russo, 2010;Feldman Barrett & Russell, 1998;Kawahara & Sato, 2013;Russell, 2003;Posner, Russell & Peterson, 2005).…”
Section: Classificationmentioning
confidence: 99%
“…Within the affective space of Russell's circumplex, fatigue is lowest in arousal and has neutral or slightly negative valence (Feldman Barrett & Russell, 1998;Kawahara & Sato, 2013). Fatigue can manifest both physiologically and cognitively (Sharpe & Wilks, 2002;Carney, Moss, Lachowski & Atwood, 2010).…”
Section: Fatiguementioning
confidence: 99%
“…Over the last two decades, an increasing number of studies have demonstrated the impact of mood states on cognitive functioning (e.g., Forgas, 2008;Kawahara & Sato, 2013;Lupien, Maheu, Tu, Fiocco, & Schramek, 2007;Matsumoto, Hwang, & Frank, 2016;Schmid & Schmid, 2010;Schwarz, 1990). A variety of procedures have been used to manipulate mood states, such as immersing participants' hands in icy water, exposing participants to joyful or dreary music, and asking participants to give a speech in front of an audience.…”
Section: Introductionmentioning
confidence: 99%